2019
DOI: 10.1016/j.dam.2019.05.005
|View full text |Cite|
|
Sign up to set email alerts
|

A rounding theorem for unique binary tomographic reconstruction

Abstract: Discrete tomography deals with the reconstruction of images from projections collected along a few given directions. Different approaches can be considered, according to different models. In this paper we adopt the grid model, where pixels are lattice points with integer coordinates, X-rays are discrete lattice lines, and projections are obtained by counting the number of lattice points intercepted by X-rays taken in the assigned directions.We move from a theoretical result that allows uniqueness of reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Their result implies that arbitrary function values can be given to a certain set of points and that thereafter the function values of the other points of A are uniquely determined by the line sums. This was made explicit by Dulio and Pagani [9] and serves as a building block in this paper.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their result implies that arbitrary function values can be given to a certain set of points and that thereafter the function values of the other points of A are uniquely determined by the line sums. This was made explicit by Dulio and Pagani [9] and serves as a building block in this paper.…”
Section: Introductionmentioning
confidence: 92%
“…Since M = 23, N = 17, there are six pixels where the choice is free, e.g. the pixels (0, 9), (0, 10),(1,9),(1,10),(2,9),(2,10). Any other 3 by 2 block of dark grey pixels can be chosen instead.…”
mentioning
confidence: 99%
“…There are methods, such as the Hough transform [11,12], with voting bins, which may be more efficient. Another family of methods relies on Dirac lattices and lines of rational slope [13,14] which can be also of interest, for example, for reconstructions with just a few projections [15].…”
Section: Introduction 1radon Transform Use and Algorithms For Its Com...mentioning
confidence: 99%
“…Furthermore, they showed that arbitrary values can be assigned to a subset of the switching domain, which allows unique values to be applied to all other points. This fact was exploited by Dulio and Pagani in [6], wherein a rounding theorem was proven which allowed exact and unique binary tomographic reconstructions from the minimum Euclidean norm solution. It also motivated the construction of boundary ghosts by Ceko, Petersen, Svalbe and Tijdeman [2].…”
Section: Introductionmentioning
confidence: 99%